THE USE OF ENGLISH-LANGUAGE STICKERS IN VIRAL EATERIES TO INCREASE YOUNG PEOPLE'S INTEREST IN LEARNING ENGLISH IN DENPASAR - Sumartini, Ni Luh Putu Unix; Vinaya, Ni Luh Made; Utami, Luh Putu Rika (LITERA : Jurnal Bahasa Dan Sastra, 2026)
English is an international language that plays a vital role in the era of globalization, particularly in tourism, education, and the professional world. However, English proficiency among young people in Indonesia, including those in Denpasar, still faces several challenges. One major obstacle is limited vocabulary mastery, which hinders their ability to understand texts, follow conversations, and express ideas both orally and in writing. This condition often reduces students’ confidence to use English in daily communication. Therefore, innovative strategies are needed to enhance vocabulary acquisition in a simple, engaging, and youth-oriented way. This study introduces the use of English-language stickers as a medium for incidental learning in public spaces, specifically at three popular dining spots in Denpasar—Kopi Jaya, Nasi Jinggo Bu Jero, and Nasi Jinggo Gundul. These stickers serve not only as aesthetic elements but also as educational tools that present simple and contextual vocabulary that is easy to comprehend. Due to their visual and repetitive nature, as well as their closeness to young people’s social environments, the stickers are expected to stimulate intrinsic motivation and strengthen vocabulary internalization. The research applies a qualitative approach supported by simple quantitative data using a One-Group Pretest-Posttest design. Data were collected through observation, interviews, questionnaires, and documentation. The objectives are to (1) identify factors contributing to low English vocabulary proficiency among young people in Denpasar, (2) examine the role of stickers as an incidental learning medium, and (3) evaluate the effectiveness of English stickers in public spaces in enhancing motivation to learn English. The findings are expected to contribute meaningfully to students by improving vocabulary and motivation, to teachers as an alternative non-formal learning strategy, and to future researchers as a reference for developing simple, low-cost, and impactful learning media that connect formal learning with real-life experiences.